Performance modelling and validation on the co-gasification of coal and sawdust pellet in research-scale downdraft reactor - Fatin Zafirah, Mansur; C. K. M., Faizal; Atnaw, Samson M.; Shaharin Anwar, Sulaiman (Universiti Sains Malaysia, 2019)
Co-gasification of fossil fuel with biomass is considered a very promising clean energy option in reducing greenhouse gas emissions and non-renewable energy dependency. The main objective of this research was to develop a simple and reliable model as a preliminary tool to evaluate the performance of co-gasification of subbituminous coal with densified biomass (sawdust pellet). The simulation model was validated experimentally to ascertain the performance parameters. The model, which included the minimization of the Gibbs free energy, was simulated using Aspen Plus as the modelling tool. Experimental investigations were carried out under controlled conditions of the electrically-driven externally-heated fixed bed downdraft gasifier in the Biomass laboratory in the Department of Mechanical Engineering, Universiti Teknologi Petronas. The operating parameter of the biomass blending ratio, gasification temperature and equivalence ratio (ERair) on the co-gasification performance parameter were analysed. Three performance parameters, calorific value of the syngas (CVsyngas), syngas yield (Ysyngas) and gasification efficiency (ŋGE), were studied. The experimental works of the co-gasification took place with air, at the various sawdust pellet blending ratios of 0, 25, 50, 75, 100% w/w, in a gasification temperature ranging from 650 to 850°C, and various air equivalence ratios ranging from 0.1 to 0.4 and under atmospheric pressure.